Otaku vampire's love bite. 4 - Suzuki, Julietta (VIZ Media, LLC, 2025)
Some vampires live to feast on the blood of their victims. Others just want to score super limited edition anime merch! Hina Alucard is a modern vampire who drinks blood from bags instead of from humans. But she's also a complete shut-in who hasn't left the house in 30 years. In an effort to reach her, Hina's dad does something that changes her life-he gives her a DVD of the Vampire Cross anime! Hina is instantly obsessed, especially with the character Mao. But it's difficult to fangirl as hard as she wants from her bedroom in Romania, so now Hina is out of the house and off to Japan to live her otaku dream! Kyuta might be Hina's best friend, but her real focus will always be Mao. So why does she feel weird when a cute girl asks Kyuta out? And Kyuta just thinks of Hina as the annoying otaku next door-it's none of his business what she does in her personal life. So why does he want to throttle his buddy when he starts hitting on her? With their thoughts in such turmoil, how will the two of them manage when they stumble face-first into some mysterious vampire business?!